On nonhomogeneous geometric quadratic stochastic operators - Karim, Siti Nurlaili (Scientific and Technical research Council of Turkey, 2022)
In this paper, we construct a nonhomogeneous geometric quadratic stochastic operator generated by 2-partition on countable state space . The limiting behavior of such operator is studied. We have proved that such operator possesses the regular property.